PENDAMPINGAN PELAKSANAAN BIMBINGAN BELAJAR BERBASIS MULTIPLE INTELLIGENCE UNTUK ABK DI SDM 2/MIM KOTA MAGELANG - Arie Supriyatno (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2018)
University Partnership Program aims to improve teachers' knowledge and experience in implementing multiple intelligence-based on learning services for children with special needs. Objectives are achieved by training methods, mentoring and practice of guidance services to 8 inclusive school teachers in SD Muhammadiyah 2 and Madrasah Ibtidaiyah Magelang. Stages of activity begins with teacher training in a multi-intelligence based on learning service for children with special needs to mentoring the implementation of learning guidance conducted for 3 months (January - March 2018). Through these activities, the more teachers know, the more teachers have skills in providing services based on multiple intelligences especially potentials student. Based on the results of university partnership program can be concluded this activity can improve the knowledge, understanding and skills of teachers in the implementation of learning guidance services to students especially children with special needs.